Relative fitness in laboratory mice of drug resistant and drug-sensitive field isolates of Trypanosoma congolense - Coleman, P.G.; Eisler, M.C.; McDermott, John J.; Murphy, N.B.; Majiwa, Phelix A.O.; Peregrine, A.S. (International Society for Veterinary Epidemiology and Economics, 2000)
Chemotherapy is the single most important strategy for the control of trypanosomosis in African livestock. Trypanocidal drug resistance is a growing problem across much of sub-Saharan Africa and increasingly recognised as a major threat to livestock production. It is therefore of pressing importance to identify effective ways of slowing the spread of resistance to available trypanocidal drugs, especially as it is unlikely that new chemotherapeutic products will become available in the foreseeable future. Generally, resistance is assumed to reduce the Darwinian fitness of pathogens in the absence of drugs. By this reasoning, a commonly accepted strategy to reverse the spread of resistance is to decrease the use of drugs. However, the evolutionary costs associated with resistance may decline over time due to other selective pressures. Recent in vivo and in vitro experiments on bacteria and viruses have shown that evolution in the absence of the selective drug can result in the rapid fixation of second-sire compensatory mutations that ameliorate the fitness costs associated with drug resistance. These observations challenge the widespread view that the frequency of drug-resistant pathogens will decline if drug usage is reduced and have important implications for policies aimed at alleviating drug resistance. To date, there has been no experimental evaluation of the fitness costs associated with drug resistance in trypanosomes. Here, we use a standardised in vivo mouse inoculation assay to define the drug sensitivity of field stabilates of Trypanosoma congolense and assess the fitness of parasites in the absence of any trypanocidal drugs. Fitness was measured as the time to establishment of a patent infection following the introduction of a standardised inoculum in control mice used in the assay. Survival analysis was used to investigate any differences in establishment time of patent infections for drug-resistant and drug-sensitive stabilates.